A Continuous Deviation-Flow Location Problem for an Alternative-Fuel Refueling Station on a Tree-Like Transportation Network - Sang Jin Kweon; Seong Wook Hwang; Jose A. Ventura (Journal of Advanced Transportation)
Due to the increasing popularity of alternative-fuel (AF) vehicles in the last two decades, several models and solution techniques have been recently published in the literature to solve AF refueling station location problems. These problems can be classified depending on the set of candidate sites: when a (finite) set of candidate sites is predetermined, the problem is called discrete; when stations can be located anywhere along the network, the problem is called continuous. Most researchers have focused on the discrete version of the problem, but solutions to the discrete version are suboptimal to its continuous counterpart. This study addresses the continuous version of the problem for an AF refueling station on a tree-type transportation network when a portion of drivers are willing to deviate from their preplanned simple paths to receive refueling service. A polynomial time solution approach is proposed to solve the problem. We first present a new algorithm that identifies all possible deviation options for each travel path. Then, an efficient algorithm is used to determine the set of optimal locations for the refueling station that maximizes the total traffic flow covered. A numerical example is solved to illustrate the proposed solution approach.